Answer:
see explanation
Step-by-step explanation:
5x² + 5x + 3 = 0 ← in standard form
with a = 5 , b = 5 , c = 3
Solve using the quadratic formula
x = ![\frac{-b+/-\sqrt{b^2-4ac} }{2a}](https://tex.z-dn.net/?f=%5Cfrac%7B-b%2B%2F-%5Csqrt%7Bb%5E2-4ac%7D%20%7D%7B2a%7D)
= ![\frac{-5+/-\sqrt{5^2-(4(5)(3)} }{2(5)}](https://tex.z-dn.net/?f=%5Cfrac%7B-5%2B%2F-%5Csqrt%7B5%5E2-%284%285%29%283%29%7D%20%7D%7B2%285%29%7D)
= ![\frac{-5+/-\sqrt{25-60} }{10}](https://tex.z-dn.net/?f=%5Cfrac%7B-5%2B%2F-%5Csqrt%7B25-60%7D%20%7D%7B10%7D)
= ![\frac{-5+/-\sqrt{-35} }{10}](https://tex.z-dn.net/?f=%5Cfrac%7B-5%2B%2F-%5Csqrt%7B-35%7D%20%7D%7B10%7D)
= ![\frac{-5+/-\sqrt{-1(35)} }{10}](https://tex.z-dn.net/?f=%5Cfrac%7B-5%2B%2F-%5Csqrt%7B-1%2835%29%7D%20%7D%7B10%7D)
= ![\frac{-5+/-i\sqrt{35} }{10}](https://tex.z-dn.net/?f=%5Cfrac%7B-5%2B%2F-i%5Csqrt%7B35%7D%20%7D%7B10%7D)
Then
x =
±
i
, that is
x = -
-
i
, -
+
i![\sqrt{35}](https://tex.z-dn.net/?f=%5Csqrt%7B35%7D)
Answer:
x=5
Step-by-step explanation:
We simplify the equation to the form, which is simple to understand
3x+5-5=20-5
We move all terms containing x to the left and all other terms to the right.
+3x=+20-5-5+5
We simplify left and right side of the equation.
+3x=+15
We divide both sides of the equation by 3 to get x.
x=5
Answer: 4 for the first one and 4.25
Explanation:
If you like this don’t forget to thank me and brilliant
Least to greatest would be 1/5 , 0.23 , and then 2.30%